2021
DOI: 10.3390/children8090735
|View full text |Cite
|
Sign up to set email alerts
|

Is Longstanding Congenital Muscular Torticollis Provoking Pelvic Malalignment Syndrome?

Abstract: It has been reported that congenital muscular torticollis (CMT) may result in secondary scoliosis over long-term follow-ups. However, there are few reports on whether CMT causes pelvic malalignment syndrome (PMS). This study aimed to investigate the relationship between CMT and PMS and to determine the factors associated with the development of PMS in children with longstanding CMT. Medical records of 130 children with CMT who had long-term follow-up were reviewed retrospectively. The chi-squared test and logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, in the specialized literature, torticollis is recognized as a possible cause of body asymmetries. A retrospective study conducted on a sample of 130 children with congenital muscular torticollis showed that 39.22% of them developed pelvic misalignment syndrome over time, with or without compensatory scoliosis [9], a conclusion also reached by Wilczyński J. in his study [58].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, in the specialized literature, torticollis is recognized as a possible cause of body asymmetries. A retrospective study conducted on a sample of 130 children with congenital muscular torticollis showed that 39.22% of them developed pelvic misalignment syndrome over time, with or without compensatory scoliosis [9], a conclusion also reached by Wilczyński J. in his study [58].…”
Section: Discussionmentioning
confidence: 72%
“…With the SCM contraction, the range of motion at the neck level is limited (LOM) [7], causing a rotation of the face to the contralateral side and homolateral head tilt [8]. The etiology and pathogenesis of congenital muscular torticollis (CMT) are not fully understood [9], with pelvic presentation, cord circling, birth trauma, and vacuum or forceps applications being incriminated [6,10]. The etiology of acquired (postnatal) torticollis (AMT) can be environmental, induced by craniosynostosis (plagiocephaly), or induced by preferential positions, in case of cerebral palsy, Down syndrome, myelodysplasia, and dysfunction of the C1 occiput-cervical area [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a genetic link between scoliosis and cervical dystonia has been suggested due to a higher prevalence of adolescent-onset scoliosis among patients with primary adult-onset cervical dystonia compared to the general population [ 10 ]. Patients with congenital cervical dystonia often develop secondary cervicothoracic scoliosis [ 11 , 12 ], which may result in secondary scoliosis in the long term. The reasons for this correlation are not fully understood, but it may be that the same genetic or developmental factors that lead to a higher risk of scoliosis also increase the risk of cervical dystonia.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, manual therapy treatment appears to offer beneficial results when focusing on mobilization of the upper cervical region and correction of cranial deformities [8,21], this circumstance stands out in research focused on children with plagiocephaly that appears associated with CMT [16], taking into account that CMT could lead to secondary alterations such as facial asymmetry, scoliosis and other alterations of the spine [7,22]. Also, some studies suggest that limitation in the neck can lead to pelvic dysfunction due to changes in posture and ability to move [9].…”
Section: Discussionmentioning
confidence: 99%
“…This disorder is the third of the pathologies that most affects the functionality of the children, behind congenital hip dysplasia and congenital clubfoot [4]. Specifically, the reported incidence of CMT ranges from 0.2% to 2% [2,4,9]. It can be considered more frequent in primiparous and with a certain predominance of the right side [4].…”
Section: Introductionmentioning
confidence: 99%